Toothbrushing abrasion susceptibility of enamel and dentin bleached with calcium-supplemented hydrogen peroxide gel - Borges, A. B. [UNESP]; Santos, L. F. T. F. [UNESP]; Augusto, M. G. [UNESP]; Bonfiette, D. [UNESP]; Hara, A. T.; Torres, C. R. G. [UNESP] (Elsevier B.V., 2016)
The objective of this study was to evaluate enamel and dentin susceptibility to toothbrushing abrasion, after bleaching with 7.5% hydrogen peroxide (HP) gel supplemented or not with 0.5% calcium gluconate (Ca). Toothbrushing was performed immediately and 1 h after bleaching, with two suspensions (high and low abrasivity). Bovine enamel and dentin specimens were divided into 12 groups (n = 10) according to the bleaching gel (with and without Ca), slurry abrasivity (high or low) and elapsed time after bleaching (immediately and after 1 h). As control, a group was not bleached, but abraded. The treatment cycle (7 d) consisted of bleaching (1 h) and toothbrushing (135 strokes/day) immediatelly or after 1 h of artificial saliva exposure. Surface roughness and surface loss (mu m) were measured by profilometry and analysed by three-way ANOVA (5%). Surface roughness means were significantly influenced by slurry abrasivity (p < 0.0001). For enamel loss, significant triple interaction was observed (p < 0.0001). HP-bleached groups and immediately brushed with high-abrasive slurry exhibited increased loss (1.41 +/- 0.14) compared to other groups (mm). Control and HP + Ca-bleached groups brushed after 1 h with low abrasive slurry presented the lowest loss (0.21 +/- 0.03/0.27 +/- 0.02). For dentin loss, significant interaction was observed for bleaching and interval factors (p < 0.001). 7.5% HP-bleached groups and immediately brushed showed significantly higher loss (8.71 +/- 2.45) than the other groups. It was concluded that surface roughness increased when high abrasive was used, independently of bleaching. 7.5% HP increased enamel and dentin loss, mainly with high abrasive slurries. Calcium supplementation of bleaching gel reduced surface loss. Additionally, in order to minimize tooth wear susceptibility, it is recommended to delay brushing after bleaching. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Enamel; Dentin; Tooth bleaching; Hydrogen peroxide; Tooth abrasion